Ethical AI Development for Sustainable Enterprises: A Review of Integrating Responsible AI with IoT and Enterprise Systems - Akter , Sohana (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
The integration of Artificial Intelligence (AI) and the Internet of Things (IoT) with enterprise systems presents immense potential for driving innovation and efficiency across various industries. However, the rapid adoption of these technologies raises ethical concerns, particularly around data privacy, bias, transparency, and environmental sustainability. This review examines the development of ethical AI in the context of sustainable enterprises, focusing on how responsible AI practices can be effectively integrated with IoT and enterprise systems to achieve long-term business value while adhering to ethical standards. By analyzing key frameworks, challenges, and case studies, this paper provides insights into fostering responsible AI development that aligns with organizational goals and global sustainability efforts.